THE EFFECT OF ENVIRONMENTAL, SOCIAL, AND GOVERNANCE DISCLOSURE ON PROFITABILITY (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to analyze the effect of Environmental, Social, and Governance (ESG) disclosure on the profitability of food and beverage companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. The sample was determined using purposive sampling, resulting in 40 companies with a total of 120 observations during the research period. The data used are secondary data obtained from annual reports and sustainability reports available on the official IDX website and company official website. The independent variable is ESG disclosure, measured using the Global Reporting Initiative (GRI) Standards 2021, while the dependent variable is profitability, proxied by Return on Assets (ROA). Firm size, leverage, and sales growth are also included as control variables. Data analysis was conducted using panel data regression with the assistance of EViews 12 software. The results indicate that environmental, social, and governance disclosures have no significant effect on profitability. This finding suggests that each ESG dimension individually has not yet contributed meaningfully to the financial performance of food and beverage companies during the research period.